SOSIALISASI FIQH ZAKAT MĀL: ZAKAT EMAS-PERAK, PERDAGANGAN, PERTANIAN DAN PETERNAKAN - Sandra Lavenia; Mugni Muhit (Jurnal Istimā, 2025)
Zakat māl is an Islamic obligation that carries both spiritual and social functions in wealth distribution, yet public literacy and implementation remain relatively low. This study aims to provide a systematic understanding of the types of zakat māl along with their nisab, haul, and required rates to support proper application based on Islamic law. The research uses a descriptive qualitative method through a literature review of classical fiqh references and relevant academic studies. The findings indicate that zakat māl includes zakat on gold, silver, trade, agriculture, and livestock. Zakat on gold, silver and trade is imposed at 2.5% after reaching nisab and haul, agricultural zakat ranges from 5–10% depending on the irrigation method, while livestock zakat follows specific nisab and quantity standards. Adequate understanding of these guidelines may improve muzakki compliance and strengthen the role of zakat as an instrument for poverty reduction and economic empowerment.